Sex-Specific Effect of Serum Lipids and Body Mass Index on Psychotic Symptoms, a Cross-Sectional Study of First-Episode Psychosis Patients - Gjerde, Priyanthi B.; Simonsen, Carmen E.; Lagerberg, Trine V.; Steen, Nils Eiel; Andreassen, Ole A.; Steen, Vidar M.; Melle, Ingrid (Frontiers in Psychiatry, 2021)
Background: Schizophrenia is a disorder with considerable heterogeneity in course and outcomes, which is in part related to the patients' sex. Studies report a link between serum lipids, body mass index (BMI), and therapeutic response. However, the role of sex in these relationships is poorly understood. In a cross-sectional sample of first-episode psychosis (FEP) patients, we investigated if the relationship between serum lipid levels (total cholesterol, HDL-C, LDL-C, and triglycerides), BMI, and symptoms differs between the sexes. Methods: We included 435 FEP patients (males: N=283, 65%) from the ongoing Thematically Organized Psychosis (TOP) study. Data on clinical status, antipsychotics, lifestyle, serum lipid levels, and BMI were obtained. The Positive and Negative Syndrome Scale (PANSS) and the Calgary Depression Scale for Schizophrenia (CDSS) were used to assess psychotic and depressive symptoms. General linear models were employed to examine the relationship between metabolic variables and symptomatology. Results: We observed a female-specific association between serum HDL-C levels and negative symptoms (B=-2.24, p=0.03) and between triglycerides levels (B=1.48, p=0.04) and BMI (B=0.27, p=0.001) with depressive symptoms. When controlling for BMI, only the association between serum HDL-C levels and negative symptoms remained significant. Moreover, the HDL-C and BMI associations remained significant after controlling for demography, lifestyle, and illness-related factors. Conclusion: We found a relationship between metabolic factors and psychiatric symptoms in FEP patients that was sex-dependent.